1978
DOI: 10.1073/pnas.75.3.1591
|View full text |Cite
|
Sign up to set email alerts
|

Neurons containing beta-endorphin in rat brain exist separately from those containing enkephalin: immunocytochemical studies.

Abstract: Well-characterized antisera to porcine #l-endorphin were used to localize immunoreactive sites in cryostat sections of formaldehyde-fixed rat brain by indirect immunohistochemistry. Specificity was established by absorption of immune sera with synthetic peptide fragments. Specific immunoreactivity was localized to neuronal perikarya in the basal tuberal hypothalamus, and to varicose nerve fibers which were distributed to midline nuclear areas throughout the diencephalon and anterior pons. These patterns of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
140
3
2

Year Published

1979
1979
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 510 publications
(156 citation statements)
references
References 34 publications
(38 reference statements)
11
140
3
2
Order By: Relevance
“…Neurons containing β-endorphin were located bilaterally in the ARC. This observation was consistent with earlier findings (Bloom et al, 1978;Finley et al, 1981). We did not detect a difference in the average number of neurons containing β-endorphin in the ARC between EA-treated and the control groups ( Table 1).…”
Section: Immunohistochemical Labeling With C-fos + β-Endorphin In Arcsupporting
confidence: 93%
See 2 more Smart Citations
“…Neurons containing β-endorphin were located bilaterally in the ARC. This observation was consistent with earlier findings (Bloom et al, 1978;Finley et al, 1981). We did not detect a difference in the average number of neurons containing β-endorphin in the ARC between EA-treated and the control groups ( Table 1).…”
Section: Immunohistochemical Labeling With C-fos + β-Endorphin In Arcsupporting
confidence: 93%
“…Separate neurons contain each of these peptides (Bloom et al, 1978). Pan et al (1996) suggested that activated neurons containing β-endorphin in the ARC may be involved in analgesia induced by EA at Zusanli acupoints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess changes in endogenous brain ␤-endorphin secretion, a local microdialysis method was utilized which has recently been shown to accurately indicate CNS responses to noxious stimuli such as formalin (Zangen et al 1998). The microdialysis site selected, the hypothalamic arcuate nucleus, is the primary, nearly exclusive, source of ␤-endorphin in the CNS, and ramifies extensively throughout the brain, with particularly dense innervation in pain modulatory regions of the periaqueductal gray and brainstem, and along the walls of the adjacent third ventricle (Bach 1997;Bloom et al 1978;Zakarian and Smyth 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess changes in endogenous brain ␤-endorphin secretion, a local microdialysis method was utilized which has recently been shown to accurately indicate CNS responses to noxious stimuli such as formalin (Zangen et al 1998). The microdialysis site selected, the hypothalamic arcuate nucleus, is the primary, nearly exclusive, source of ␤-endorphin in the CNS, and ramifies extensively throughout the brain, with particularly dense innervation in pain modulatory regions of the periaqueductal gray and brainstem, and along the walls of the adjacent third ventricle (Bach 1997;Bloom et al 1978;Zakarian and Smyth 1982).Previous studies in our and other laboratories have demonstrated that transplants of adrenal medullary chromaffin cells into the subarachnoid space of the spinal cord can attenuate pain responses in a variety of animal models and offers a promising avenue for clinical pain management (Brewer and Yezierski 1998;Buchser et al 1996;Burgess et al 1996;Décosterd et al 1998;Hains et al 1998;Hama and Sagen 1993;Lazorthes et al 1995;Ortega-Alvaro et al 1997;Sagen et al 1990;Siegan and Sagen 1997;Vaquero et al 1991;Winnie et al 1993;Yu et al 1998). Although the transplanted cells appear to produce some of their antinociceptive effects via local release of pain-reducing analgesic agents, including catecholamines and opioid peptides, into the host spinal CSF (Sagen and Kemmler 1989;Sagen et al 1991), recent studies have indicated that these transplants can also produce neuroplastic changes in the pain processing circuitry of the spinal cord, including restoration of spinal inhibitory neurons and decreased c-fos activation in response to persistent pain (Ibuki et al 1997;Sagen and Wang 1995).…”
mentioning
confidence: 99%